Synthesis, evaluation, molecular dynamics simulation and targets identification of novel pyrazole-containing imide derivatives. Issue 6 (31st March 2021) - Cai, Wenxi; Wu, Jingwei; Sun, Yingzhan; Liu, Ailin; Wang, Runling; Ma, Ying; Shuqing Wang,; Dong, Weili
Abstract: A new series of novel pyrazole-containing imide derivatives were synthesized and evaluated for their anticancer activities against A-549, Bel7402, and HCT-8 cell lines. Among these compounds A2, A4, A11 and A14 possessed high inhibition activity against A-549 cell lines with IC50 values at 4.91, 3.22, 27.43 and 18.14 μM, respectively, better than that of 5-fluorouracil (IC50 =59.27 μM). A2, A4, and A11 also exhibited significant inhibitory activity towards HCT-8 and Bel7402 cell lines. Interestingly, the Heat Shock Protein 90α (Hsp90α, PDB ID: 1UYK) was found to be the potential drug target of these synthesized compounds with the aid of PharmMapper server (http://lilab.ecust.edu.cn/pharmmapper/ ) and docking module of Schrödinger (Maestro 10.2). Additionally, molecular dynamics simulation was performed out to explore the most likely binding mode of compound A2 with Hsp90α. Communicated by Ramaswamy H. Sarma